1977
DOI: 10.1111/j.1464-410x.1977.tb04089.x
|View full text |Cite
|
Sign up to set email alerts
|

Cinoxacin concentrations in Plasma, Urine and Prostatic Tissue after Oral Administration to Man

Abstract: Cinoxacin, a synthetic antibacterial compound, was given orally in a dose of 500 mg to 8 patients undergoing transurethral prostatectomy. The drug was well absorbed and the peak plasma level (mean 13.9 mcg/ml) occurred 1 or 2 hours after administration. Concentrations of cinoxacin in the urine reached a peak (mean 236.5 mcg/ml) 4 to 6 hours after dosing, and remained higher than the mean MIC for most common urinary pathogens for 12 hours after administration. The concentration of cinoxacin in prostatic tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Serum and urinary levels, as well as pharmacokinetic parameters of Cinoxacin determined in this study are in agreement with the data reported in the literature (1,2,3, 6,7,13,15,20). For pipemidic acid however we have found a larger percentage of urinary recovery (83% over 24 h) than cited by Humbert et al (12) (63% over 24 h) or Soussy et al (22) (48.3% over 24 h).…”
Section: Discussionsupporting
confidence: 82%
“…Serum and urinary levels, as well as pharmacokinetic parameters of Cinoxacin determined in this study are in agreement with the data reported in the literature (1,2,3, 6,7,13,15,20). For pipemidic acid however we have found a larger percentage of urinary recovery (83% over 24 h) than cited by Humbert et al (12) (63% over 24 h) or Soussy et al (22) (48.3% over 24 h).…”
Section: Discussionsupporting
confidence: 82%
“…Other investigators reported this phenomenon in patients after 0.25-g (14) and 0.5-g doses (3,4). Similar variations in peak serum concentrations and time to reach peak concentrations have been observed with other orally administered agents (7,8).…”
Section: Resultsmentioning
confidence: 98%
“…Cinoxacin (Cinobac; 1-ethyl-1,4-dihydro-4-oxo [1,3] dioxolo- [4,5-g] cinnoline-3-carboxylic acid) is a synthetic organic antibacterial which has good in vitro antimicrobial activity against Enterobacteriaceae but negligible activity against Pseudomonas aeruginosa and gram-positive cocci (5,9,10,12,13,16). As expected from in vitro activity, cinoxacin has been shown to be clinically effective in the treatment of urinary tract infections caused by these microorganisms (2, 11, 14, 15, 17; C. E. Cox, Abstr.…”
mentioning
confidence: 99%
“…Except for day 1, a. serum sample was also taken just before administration of the morning dose. Urine was collected on the same days at 3,6, and 12 h after drug administration. To evaluate the safety of the drug, the following laboratory tests were performed before and at the end of the treatment: serum creatinine, blood urea nitrogen, creatinine clearance, total bilirubin, serum glutamic-oxaloacetic transaminase, and alkaline phosphatase, as well as leukocyte count, hemoglobin, and hematocrit.…”
mentioning
confidence: 99%